Analisis Pengaruh Faktor Penentu Struktur Modal Pada Perusahaan Syariah di Indonesia - Wulandari, Refita Tri; Suryani, Ani Wilujeng (Wahana Riset Akuntansi, 2024)
Purpose – This study aims to analyze the factors that determine the capital structure consisting of profitability, asset tangibility, company size, and growth opportunities.Design/methodology/approach – As many as 216 companies listed on the Indonesian Sharia Stock Index (ISSI) from 2011 to 2021 were sampled in this study. Panel data regression analysis with a fixed effect model is used in hypothesis testing.Findings – The results indicate that all factors influence the capital structure, albeit with varying directions. Profitability has a negative effect while asset tangibility, firm size, and growth opportunities have a positive effect on capital structure. The results of this study identify that profitability, asset tangibility, company size, and growth opportunities are aspects that are considered by financial managers in determining capital structure policies.Originality/value – While studies commonly focused on the conventional companies’ capital structure, this study diverges from prior studies by examining the capital structure of companies adhering to sharia principles. This study is unique in the Indonesian setting, and hence, this study contributes to the existing literatures by exploring capital structure determination in the companies applying sharia principles.Research limitations/implications – This study contributes to the financial literature regarding capital structure, with a specific focus on companies that operate with sharia principles. According to the findings of the study, investors are expected to possess a comprehensive understanding of relevant information related to financial ratios including profitability, tangible assets, company size, and growth opportunities before making investment decisions in the capital market. In addition, financial managers must be able to optimize the value of profitability, growth, and tangible assets, which play a crucial role in determining the company's capital structure policy. However, it is common in a quantitative study that not all data can be used. Outliers had persisted in this study; thus, trimming was performed, which led to a reduction in the sample size.